Evaluation of variation in the phosphoinositide-3-kinase catalytic subunit alpha oncogene and breast cancer risk - Stevens, Kristen N.; Burwinkel, Barbara; Hamann, Ute; Chang-Claude, Jenny (British journal of cancer, 2011)
Background: Somatic mutations in phosphoinositide-3-kinase catalytic subunit alpha (PIK3CA) are frequent in breast tumours and have been associated with oestrogen receptor (ER) expression, human epidermal growth factor receptor-2 overexpression, lymph node metastasis and poor survival. The goal of this study was to evaluate the association between inherited variation in this oncogene and risk of breast cancer. Methods: A single-nucleotide polymorphism from the PIK3CA locus that was associated with breast cancer in a study of Caucasian breast cancer cases and controls from the Mayo Clinic (MCBCS) was genotyped in 5436 cases and 5280 controls from the Cancer Genetic Markers of Susceptibility (CGEMS) study and in 30 949 cases and 29 788 controls from the Breast Cancer Association Consortium (BCAC). Results: Rs1607237 was significantly associated with a decreased risk of breast cancer in MCBCS, CGEMS and all studies of white Europeans combined (odds ratio (OR)=0.97, 95% confidence interval (CI) 0.95–0.99, P=4.6 × 10−3), but did not reach significance in the BCAC replication study alone (OR=0.98, 95% CI 0.96–1.01, P=0.139). Conclusion: Common germline variation in PIK3CA does not have a strong influence on the risk of breast cancer.
Gesehen am 21.10.2022